PELAKSANAAN PEMASARAN RELASIONAL PADA RUMAH BERNYANYI PT. NAV BINA PRATAMA DI PEKANBARU - Muhadi "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Problems in the research is PT. Bima NAV Pratama family karaoke is one of the many karaoke place families in Soweto. Although more and more competitors are emerging, but the presence of PT. Bima NAV Pratama is still very attractive and welcomed in the community – pekanbaru. However, notwithstanding the number of pengnjungan has decreased, it became one of the reasons the author to do some research on PT Bima Pratama NAV as a focus of research. The higher the level of competition among peers and to the increasingly influential customer loyalty towards the entertainment venues. In this case the company should be more meticulous attention to the needs, wants and expectations of consumers, with the ability to fulfill the wishes and expectations of consumers and hopes the company itself is consumers will have loyalty and continued to do so purchase repeatedly and will not be moved to another place.As for the purpose of research is to know the execution of relational marketing at PT. Bima Nav Pratama Pekanbaru. Results of the study concluded that of the score obtained from the results of the recapitulation is in the range of 3690-4559 by category either. This indicates that commitment, empathy, reciprocity and trust given by PT Bima NAV Pratama Soweto as a karaoke service penjuala, as a whole is considered good by the respondent. It means work done by companies already applied, it's just a good effort still needed to be longer for menjali relationship with customers in order to continue to run well, so that the company's cooperation with customers relations continue within the long term.Keyword: Relational Marketing, Customer, Competitor